Interpolation par des fonctions entières: Interpolation by entire functions - Groza, Ghiocel; Pop, Nicolae (Rev. Anal. Numér. Théor. Approx., 2006)
In French. Soit \(A\) une algèbre normè unifère commutative complète sur un corps commutatif à valeur absolue non triviale. L’article montre qu’il existe une fonction entière, ayant les coefficients en \(A\) qui donne une solution pour un problème d’interpolation infinie en \(A\). In English. Let \(A\) be a complete commutative uniferous norm algebra over a nontrivial absolute value commutative field. The article shows that there exists an integer function, having the coefficients in \(A\) that gives a solution for an infinite interpolation problem in \(A\).